Ruthenium(ii) p-cymene complexes of pyridine-2-carboxaldehyde and 2-amino benzothiazole-based ligands: cytoselective and in vitro live cell imaging agents. (14th June 2021) - P. K., Anuja; Paira, Priyankar
Abstract : A new class of DNA targeting, highly cytoselective, luminescent Ru(ii )–arene complexes was developed. Abstract : Five Ru(ii )–arene complexes with the general formula [(η 6 - p -cymene)RuCl(k 1 L1-L5)(pyridine-2-carboxaldehyde)]Cl were synthesized at ambient temperature, which exhibited 8–11-fold higher cytoselectivity in two cancer cell lines (HeLa and MCF-7) compared to normal kidney cells (HEK-293). Furthermore, these complexes showed higher potency and selectivity compared to cisplatin. Among the synthesized scaffolds, the [(η 6 - p -cymene)RuCl(k 1 L3)(pyridine-2-carboxaldehyde)]Cl complex (RuL3 ) contains an –F group, which enhanced its lipophilicity, triggering its selective cellular accumulation in HeLa and MCF-7 cells, and thus it exhibited the highest cytoselectivity. The strong DNA intercalative nature of the RuL3 complex enabled its potency against the cancer cells. All the complexes displayed MLCT (metal–ligand charge transfer) emission maxima in the wavelength range of λ ems 526–535 nm, and among them, the RuL3 complex exhibited the highest quantum yield (0.32), making it an efficient in vitro live cell imaging agent.